2018
DOI: 10.1007/s13577-018-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of the NCC–SS1–C1 synovial sarcoma cell line

Abstract: Synovial sarcoma is an aggressive mesenchymal malignancy characterized by unique gene fusions. Tissue culture cells are essential tools for further understanding tumorigenesis and anti-cancer drug development; however, only a limited number of well-characterized synovial sarcoma cell lines exist. Thus, the objective of this study was to establish a patient-derived synovial sarcoma cell line. We established a synovial sarcoma cell line from tumor tissue isolated from a 72-year-old female patient. Prepared cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Prior data showed that SLC12A3 is involved in different diseases such as sarcoma, neoplasms, chondrosarcoma, and adult synovial sarcoma, respectively. 42 Similarly, KCNE1, KCNQ1, and APEX1 are linked with atrial fibrillation, 81 adenocarcinomas, 82 and adenocarcinoma of the lung. 83 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior data showed that SLC12A3 is involved in different diseases such as sarcoma, neoplasms, chondrosarcoma, and adult synovial sarcoma, respectively. 42 Similarly, KCNE1, KCNQ1, and APEX1 are linked with atrial fibrillation, 81 adenocarcinomas, 82 and adenocarcinoma of the lung. 83 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Literature reports also showed that ABCB1 has a good correlation with some diseases such as osteosarcoma of bone, childhood osteosarcoma, sarcoma of soft tissues, fibrosarcoma, adult fibrosarcoma, and peripheral primitive neuroectodermal tumor. Another report showed that the KCNH1 and HPSE genes are linked with multiple bone-associated diseases such as childhood osteosarcoma, fibrosarcoma, and synovial sarcoma. Indapamide interacts with SLC12A3, KCNE1, KCNQ1, and APEX1 with different scoring values. Prior data showed that SLC12A3 is involved in different diseases such as sarcoma, neoplasms, chondrosarcoma, and adult synovial sarcoma, respectively . Similarly, KCNE1, KCNQ1, and APEX1 are linked with atrial fibrillation, adenocarcinomas, and adenocarcinoma of the lung …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ere are a number of studies based on patient-derived cells (PDC) and patient-derived xenograft (PDX) model in vivo. However, most of the described investigations are focused on establishment of new cell line derived from patient tumor (for example, see [63][64][65][66][67], on preclinical studies of novel or repurposed drug/combination of drugs in vitro [68][69][70][71] and in vivo [72][73][74]). Only a few studies address the optimization of STS treatment.…”
Section: Drug Sensitivity Testing On Patient-derived Sts Cellsmentioning
confidence: 99%
“…It remains however unclear how well these preclinical tumor models recapitulate patient tumor biology. We therefore developed sarcoma patient‐derived models for proteomic and functional studies, and tried to assess whether PDXsretain their proteomic characteristics with successive passaging …”
Section: Introductionmentioning
confidence: 99%